The Banū Yahrāsan, Political and Sacred Leaders in Ibāḍī Djerba - Prevost, Virginie (Al-Masāq, 2021)
From the beginning of the tenth century, a strong authority whose representatives belong to the Banū Yahrāsan asserts itself in Djerba. This exclusively masculine power is at once political and religious, it is hereditary, it marks a desire for appeasement in conflicts with schismatic groups and quickly gives a certain place, unfortunately difficult to evaluate, to collegiality. According to the written sources, the Banū Yahrāsan are at the origin of the foundation of the ḥalqa, determinant for the future of the Ibāḍī Maghreb, and have left a strong imprint that survives until today in the sacred geography of the island. The writings of Sulaymān al-Ḥīlātī show how this golden age was still captivating the seventeenth-century Ibāḍīs by inviting them to gather in many buildings, mosques or mausoleums, which perpetuate to this day the memory of the Banū Yahrāsan in Djerba.
Keywords: Ḥīlātī al-Ğarbī; Sulaymān ibn Aḥmad al- (16..-1688)

ثورة باغاي "969/358": آخر انتفاضة إباضية - Prevost, Virginie (دورية كان التاريخية, 2021)
Number: 053
Keywords: Révoltes – Baghaya (Algérie)

Ghardaïa, une île ? - Prevost, Virginie; Bouali-Messahel, Mounia (2021)
Keywords: Urbanisme – Mzab

Table ronde : Ghardaïa et la tradition moderne - Prevost, Virginie; Bouali-Messahel, Mounia; Bendimerad, Sabri (2021)
Keywords: Urbanisme – Mzab